Efficacy and safety of innate and adaptive immunotherapy combined with standard of care in high-grade gliomas: a systematic review and meta-analysis - Guo, Baofeng; Zhang, Shengnan; Xu, Libo; Sun, Jicheng; Chan, Wai-Lun; Zheng, Pengfei; Zhang, Jinnan; Zhang, Ling (Frontiers in Immunology, 2023)
Background: Malignant glioma is the most common intracranial malignant tumor with the highest mortality. Currently, the survival rate and life expectancy of high-grade glioma (HGG) patients remain still an outstanding critical issue, due to the poor prognosis, easy recurrence, and rapid progression of HGGs. Therefore, it is highly pressing to find and develop more efficacious treatments for glioma. Objective: The efficacy and safety of immunotherapy in glioma were evaluated by systematic review and meta-analysis. The difference in treatment efficacy and safety of various immunotherapies towards different lesion types and therapeutic schemes were particularly explored. Method: Retrieved hits were screened for inclusion in 2,317 articles. We extracted the hazard ratio of overall survival (OS) and progression-free survival (PFS) as two key outcomes for examining the efficacy of immunotherapy. We calculated reported corresponding adverse events for assessing the safety of immunotherapy. This study was registered with PROSPERO, number CRD42019112356. Result: A total of 1271 patients, of which 524 patients received a combination of immunotherapy and SOC, and 747 patients received SOC. Immunotherapy can extend the OS (HR=0.74, 95%CI 0.56-0.99), Z=-2.00, p=0.0458<0.05) and PFS (HR=0.67, 95%CI 0.45-0.99), Z=-1.99, p=0.0466<0.05) with a substantial publication bias, given that certain adverse events occurred (proportion = 0.0773, 95% CI 0.0589-0.1014). However, our data support the efficacy of dendritic cell vaccine (DC) prolonging the OS (HR=0.38, 95% CI 0.21-0.68; Z=-3.23, p=0.0012<0.05), yet so far not for the PFS (HR=0.60, 95% CI 0.35-1.0345; Z=-1.84, p=0.0661). Our data also support the efficacy of oncolytic viral therapy (VT) since we have found that the OS can be prolonged by receiving a part of viral vaccination (HR=0.60, 95%CI 0.45-0.80), Z=-3.53, p=0.0004<0.05), although, by such means, the PFS could not be prolonged (HR=0.52, 95%CI 0.22-1.22), Z=-1.50, p=0.1343>0.05). Immunopotentiation (IP) cannot prolong the OS (HR=0.69, 95% CI 0.50-0.96; Z =-2.23, p=0.0256), nor the PFS (HR=1.20, 95%CI (0.75-1.92), Z=0.76, p=0.449>0.05). Conclusion: The efficacy of VT needs to be further studied. The treatment of DC therapy significantly prolongs the OS of HGG patients; however, IP shows no apparent effect. All the therapeutic schemes have demonstrated certain side effects, but they can all be synergized with TMZ.